Legislating what matters: How policy designs shape two new immigrant destinations schools’ responses to immigrant students - Brezicha, Kristina F. (Education Policy Analysis Archives, 2022)
This comparative case study examines the policies of two new immigrant destinations in the United States and Canada that in the past 20 years experienced a rapid influx of immigrants. Using an integrated framework of policy design theory and the context of reception, this paper analyzes the framing of immigrant students in the state, district, and school-level policies. Interviews with immigrant students in these communities show how these policies shaped their schooling experiences and communicated important messages to them about their role in their new communities, thus shaping their political identities. The findings highlight the important interplay of these different policymakers in shaping the contexts of receptions students encountered. The paper concludes by discussing educators’ role in working to craft more equitable policies.